ANALYSIS OF THE PERFORMANCE OF CASUAL WORKERS AT THE LEGAL BUREAU OF THE REGIONAL SECRETARIAT OF NORTH SULAWESI PROVINCE - Siwij, Devie; Mantiri, Jeane; Arobaya, Sherina (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2023)
This research aims to find out, analyze and describe the performance of freelance daily workers at the Legal Bureau of the Regional Secretariat of North Sulawesi Province. The research method used is descriptive qualitative. The number of informants in this study was 8 people. Data collection uses observation, interview and documentation techniques. Data analysis through data reduction, data presentation and drawing conclusions. The results of the research show that the performance of freelance daily workers at the Legal Bureau of the Regional Secretariat of North Sulawesi Province is not yet optimal in terms of four indicators: 1) the quality of performance is still low, seen from the fact that there are still employees who are careless and careless in their work, 2) knowledge about work where understanding , abilities and suitability of work with the title they have are good, 3) productivity and initiative are not yet effective and efficient, this can be seen where employees have not worked optimally where they work only on the basis of orders from superiors, have not prioritized work over personal matters and not careful in working. 4) responsibility and cooperation, employees have not been able to take responsibility for the work, this can be seen from the lack of discipline in terms of time, employees have not been able to complete the work according to the time set, each employee can provide assistance just to help and has not been able to take action. work that is their expertise and collaboration is only carried out by fellow sub-divisions. Penelitian ini bertujuan untuk mengetahui, menganalisis dan mendeskripsikan bagaimana kinerja tenaga harian lepas pada Biro Hukum Sekretariat Daerah Provinsi Sulawesi Utara. Metode penelitian yang digunakan adalah deskriptif kualitatif. Jumlah informan dalam penelitian ini sebanyak 8 orang. Pengumpulan data menggunakan teknik observasi, wawancara dan dokumentasi. Analisis data melalui Reduksi Data, Penyajian Data dan Penarikan Kesimpulan. Hasil penelitian menunjukkan bahwa kinerja tenaga harian lepas pada Biro Hukum Sekretariat Daerah Provinsi Sulawesi Utara belum optimal ditinjau dari empat indikator 1) kualitas kinerja masih rendah dilihat dari masih adanya pegawai yang kurang cermat dan tidak teliti dalam bekerja, 2) pengetahuan tentang pekerjaan dimana pemahaman pemahaman, kemampuan, dan kesesuaian pekerjaan dengan gelar yang dimiliki sudah baik, 3) produktivitas dan inisiatif belum efektif dan efisien, hal ini terlihat dimana karyawan belum bekerja secara maksimal dimana mereka bekerja hanya atas dasar perintah dari atasan, belum mengutamakan pekerjaan dari pada urusan pribadi dan belum teliti dalam bekerja. 4) tanggung jawab dan kerjasama pegawai belum dapat bertanggung jawab terhadap pekerjaan, hal ini dapat dilihat dari kurangnya disiplin dalam hal waktu, pegawai belum dapat menyelesaikan pekerjaan sesuai dengan waktu yang telah ditetapkan, setiap pegawai dapat memberikan bantuan hanya sekedar membantu dan belum dapat mengambil suatu pekerjaan yang menjadi keahliannya serta kerjasama hanya dilakukan sesama sub bagian.